COSTS OF IMPLEMENTING HEALTH PROTOCOLS, RELIABILITY, FACILITIES, ON CUSTOMER SATISFACTION AS INTERVENING VARIABLES WITH CUSTOMER LOYALTY AT GAMBIR STATION DURING THE ENDEMIC - Saidah, Deslida; Wahyuni, Rr. Endang; Subandi, Subandi; Danuarto, Danang; Nashrullah, Nashrullah (Universitas Budi Luhur, 2023)
The train is a mode of mass transportation that is very popular with the public because it is economical, comfortable, has a large transportation capacity, and travels without obstacles. Gambir Station is an executive and mixed-class train station. During the Covid-19 endemic, health protocols are still implemented. The aim of the research is to determine and analyze the influence of the costs of implementing health protocols, reliability, and facilities on customer satisfaction as an intervening variable with customer loyalty at Gambir Station during the endemic. The research method used is a qualitative descriptive method which is quantitative with path analysis. The population of this study was all train passengers at Gambir Station, while the sample was taken from train passengers using accidental sampling. The research results show that in the path analysis, namely the variable costs of implementing health protocols, reliability, and facilities directly have a significant effect on the variable customer satisfaction. The variables of reliability, facilities, and customer satisfaction directly have a significant effect on the variable of customer loyalty except for the variable cost of implementing health protocols which is not significant. Meanwhile, the influence of the costs of implementing health protocols, reliability, and facilities on customer loyalty and satisfaction is a positive intervening variable.